Strategi CSR PT Pertamina Geothermal Energy dalam meningkatkan kualitas kopi geothermal area kamojang: Strategi CSR PT Pertamina Geothermal Energy dalam meningkatkan kualitas kopi geothermal area kamojang - HAKIKI, RIDHO (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2023)
This study aims to determine the CSR Strategy of PT. Pertamina Geothermal Energy in Improving the Quality of Kamojang Geothermal Area Coffee, regarding (1) PT Pertamina Geothermal Energy's CSR Strategy Process in improving the quality of Kamojang Geothermal Area Coffee (2) Developing an organic waste management program in the Kamojang area to support sustainable agricultural practices, so as to improve soil fertility and yield quality of Kamojang Geothermal Coffee (3) Increasing market access for coffee farmers in the Kamojang area by helping them market their coffee products to a wider market, both domestically and abroad. The method used in this research is a qualitative research method with a case study approach. Data collection in this study was carried out by interviews, non-participant observation. This program covers the cultivation and processing of coffee. The scope of cultivation in question is PT. Pertamina Geothermal Energy Area Kamojang participates in increasing capacity and providing assistance in optimizing the Kamojang Area Geothermal Coffee cultivation process in farmer groups. The scope of coffee processing includes capacity building as well as providing assistance with coffee processing facilities and infrastructure for the Mount Kamojang farmer groups. Through this program, it is hoped that the company can participate in increasing the capacity of residents around Kamojang while optimizing agricultural commodities in the Kamojang area. The theory of supporting communication methods in this study is Stakeholder Theory, and CSR. Based on the research results, it was found that PT Pertamina Geothermal Energy's CSR Strategy process in improving the quality of Geothermal Coffee in the Kamojang Area was carried out by Social Mapping, Surveys, Compilation. Program, Implementation, Evaluation / Monitoring As for Developing an organic waste management program in the Kamojang area to support sustainable agricultural practices, so as to increase soil fertility and yield quality for Geothermal Coffee in the Kamojang Area As well as finding several Improve market access for coffee farmers in the Kamojang area by helping they market their coffee products to a wider market, both domestically and abroad, winning awards, for the community getting development, knowledge and skills, improving the economy and for employees getting new experiences, as a learning method. Keywords: PT Pertamina Geothermal Energy Area Kamojang CSR Strategy, Geothermal Coffee Processing Cultivation and Community Empowerment